An OGC-WS framework to run firestation on the grid - Pina, António Manuel Silva (2009)
The CROSS-Fire project aims to develop a grid-based frame- work as a risk management decision support system for the civil protection authorities, using forest fires as the main case study and FireStation as the standalone CAD application that simulates the fire spread over complex topography. The CROSS-Fire initial tasks focussed on the development of a parallel version of the fire simulator engine, P-FireStation, and its porting into the EGEE grid environment, G-FireStation. The main contribution of this communication lies on the definition of an OGC-WS framework to en- able a basic set of standard geospatial services that will allow Firestation to be interoperable with standard-based Spatial Data Infrastructures. The P-FireStation version explores the inherent parallel environment of- fered by clusters at each site of the EGEE grid, to support larger data sets and to improve the accuracy of the predictions. This parallel version relies on the MPI protocol and supports larger data sets taking advantage of the MPI parallel I/O facilities. The G-FireStation version integrates EGEE grid facilities, namely the gLite data management services and tools to access data, the AMGA gLite grid metadata catalogue to manage the sim- ulation I/O data, and the WatchDog tool to monitor and provide data for the interactive control of simulations. CROSS-Fire decision support system will be implemented as a web portal that presents at its core a layer of OGC protocols to access, add and pro- cess data: WCS for interoperable access to geospatial coverages, WFS for retrieving geographic features and WPS for geospatial processing services and control of the execution of simulations. The portal is also a connection point for desktop clients with GIS and CAD capabilities. The approach will make G-FireStation more interoperable, allowing to ac- cess different data providers and publishing output data for further pro- cessing, following the guidelines of the EC CYCLOPS project.